Implementation of E-Book Flip PDF Professional Sepak Takraw Material for High School Students - Ryan, Muhammad Dwi; Aryanti, Silvi; Bayu, Wahyu Indra; Destriani, Destriani; Solahuddin, Soleh; Azhar, Samsul; Tuti, Resti Ries (Universitas Tanjungpura, 2024)
The use of technology in supporting learning is currently massive by teachers, one of the latest technologies that is often used is e-books that make it easier for teachers to deliver learning materials. This study aims to evaluate how effective it is to use e-books based on the Flip PDF Professional application for high school students. The approach used is Classroom Action Research, consisting of three cycles, namely pre-cycle, cycle I, and cycle II. The subjects in this study were 30 students of class X1 SMA Muhammadiyah 3 Palembang. Data collection was carried out through test and observation methods carried out in several stages, namely planning, implementation, observation, and reflection. The results showed that in the pre-cycle stage, the classical completeness rate reached 30%, the average score of students was 55.6. Furthermore, the level of completeness increased by 60% and the average score was 72. Cycle II got even better results with the level of classical completeness reaching 66.6% and the average score of students increasing to 81. The conclusion of this study is that the use of e-books based on the Flip PDF Professional application for sepak takraw learning is effective for improving students' academic achievement. The use of this interactive e-book is expected to increase students' interest in learning, understanding of concepts, and skills in Sepak Takraw through a more dynamic, visual, and interactive learning experience.